A Nonhomologous End-Joining Mutant for Neurospora sitophila Research - Nicholas A Rhoades; Elise K Webber; Thomas M Hammond (Fungal Genetics Reports, 2020)
Disruption of the nonhomologous end-joining (NHEJ) pathway has been shown to increase the efficiency of transgene integration into targeted genomic locations of Neurospora crassa and other fungi. Here, we report that a similar phenomenon occurs in a second Neurospora species: N. sitophila. Specifically, we show that deletion of N. sitophila mus-51 increases the efficiency of targeted-transgene integration, presumably by disrupting NHEJ. Researchers interested in obtaining the N. sitophila mus-51∆ strains described in this study can obtain them from the Fungal Genetics Stock Center (FGSC, Kansas State University, Manhattan, KS).
Keywords: Neurospora; NHEJ; nourseothricin; sitophila; transformation